Investigation of Japanese electricity industry using a CGE model of translog function - Kwang Il Kim (Journal of Economic Structures, 2019)
CGE models are usually used for policy analysis. The conventional CGE models use CES function because of being a convenience for modeling. Moreover, some of the CGE models use a multi-CES function to model the multi-layered production process. These multi-layered CES functions are frequently used in the energy and environmental policy analysis. However, the CES function is rigid for considering various substitution- complement relationships. In this regard, this study suggests another type of CGE model that uses the translog function for modeling of power generation. Taking the model into practice, we analyze the effects of the carbon tax on power generation in substitution and complement scenarios, as an application. We compare three carbon tax scenarios (289 Yen as BAU, 600 Yen, and 2000 Yen/CO2 ton) to investigate the impact of carbon tax on power generation. The results of the simulation show that industrial production decreases and substitution of the power sources for thermal power generation being significant in response to a carbon tax increase. Moreover, the result suggests that the translog function model is available for analysis of electricity industry under environmental policies.
Keywords: 330; Computable general equilibrium; Translog function; Electricity industry; Substitution; Complement